Manik Buangsi - Angeles, Alberta; Crisostomo, Ibarra Cruz (Quezon City Children's Communication Center, 1983)
A Samal folktale about the love between a mortal and an immortal.
For grade 3.
Keywords: Children's stories, Philippine (English); Children's stories, Filipino; Folk literature, Philippine (English).